A difficult case of subacromial bursitis in diabetes treated by steroid injection and physiotherapy combined with yoga - Vijay Pratap Singh; Bidita Khandelwal; Namgyal T Sherpa (Indian Journal of Pain, 2013)
Subacromial injections of steroid when given accurately to the subacromial space followed by appropriate physiotherapy and yoga resulted in significantly reduced pain and increased functional outcomes in subacromial bursitis in a type II diabetes patient. Steroidal injections wherever indicated and if injected correctly into the subacromial space under proper sterile condition leads to enhanced healing, reduced pain, improved range of motion, and increased functional ability and return to work. In situations of doubt, ultrasonography (USG) or magnetic resonance imaging (MRI) can provide better insight to its pathology and site which in turn helps the clinician to take correct decisions about injection therapy, drug, and approach to be used. Inaccurately administered injections may delay the healing process and burden the patient further to undergo surgical intervention. It is better to use physiotherapy exercises and yoga asanas as adjuvant to enhance recovery and functions after injection therapy.